Tubular and glomerular kidney effects in the Chinese general population with low environmental cadmium exposure. (March 2016) - Wang, Dongyue; Sun, Hong; Wu, Ye; Zhou, Zhengyuan; Ding, Zhen; Chen, Xiaodong; Xu, Yan
Abstract: Cadmium (Cd), a well-known nephrotoxic agent, has received a great deal of attention from the Chinese public because of reports of its presence in rice. But very few studies have assessed the renal risk of Cd exposure in children. In this cross-sectional study, we aimed to determine whether biologic measures of Cd exposure were associated with biomarkers of early kidney damage in children, adolescents and adults. A total of 1235 subjects (2–86.8 years old) participated in this study and provided samples of blood and urine. As a result, the median urinary Cd level was 0.38 μg g −1 creatinine in adult men and 0.42 μg g −1 creatinine in adult women, similar to reference values observed in the United States (median: 0.32–0.40 μg L −1 in adults). Multiple linear regressions showed Cd in urine to be significantly positively associated with effects on renal tubule biomarkers (as indicated by increased levels of N-acetyl-β-d -glucosaminidase and β2-microglobulin) after adjusting for age, body mass index, blood lead, and urinary density, in all age groups including children. We also found positive associations between blood Cd and renal tubule biomarkers in children. In conclusion, adverse tubular renal effects might have occurred at the current low Cd levels in the study population, including children. These findings are particularly relevant assessing health risks associated with low environmental exposures to Cd. Highlights: Cadmium in urine and blood were positively associated with tubular biomarkers even in children. N-acetyl-β-d -glucosaminidase in urine was a very sensitive biomarker of cadmium exposure. Cadmium in urine or blood was not associated with a decreased glomerular filtration rate.